Real-Time Dynamic Voltage Scaling for the EPOS Operating System - Meira, Gustavo Nardon; Fröhlich, Antônio Augusto; Hoeller Jr., Arliones (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
Several implementations of Real-Time Dynamic Voltage and Frequency Scaling (RT-DVFS) have been made in the last decade. Most of them, however, are adaptations performed over some Linux-based operating system. The real-time support on Linux systems depend on complex modifications of the system kernel and is often not regarded as hard real-time support. This work presents the design and implementation of the DVFS support for the hard real-time schedulers of EPOS (Embedded Parallel Operating System) -- an application-driven operating system designed to support embedded applications. The design presented here supports the insertion of RT-DVFS heuristics into the system schedulers in a loosely-coupled fashion. The design is implemented in EPOS and evaluated in a XScale processor. Effectiveness of the RT-DVFS heuristic is assessed by implementing two classic RT-DVFS algorithms that were proposed as extensions to the Earliest Deadline First scheduler.